Tubomanometry correlations with patient characteristics and other diagnostic tests of Eustachian tube dysfunction: a cohort study of 432 ears - Oehlandt Heidi; Lindfors Oskari; Sinkkonen Saku T (SPRINGER, 2022)
Objectives
Currently, there is no consensus regarding the best protocol for diagnosing Eustachian tube dysfunction (ETD). We aimed to evaluate how patient characteristics affect tubomanometry (TMM) results. If an association between patient characteristics and TMM results exists, this should be considered in TMM interpretation. We also wanted to study if TMM correlates with other diagnostic tools of ETD.
Methods
A retrospective chart review was conducted on all patients with TMM results available from November 2011 to October 2020 at a tertiary referral center, including 432 ears from 219 patients. An association between diagnostic tests and patient characteristics was assessed using regression models. Spearman's rank correlation was used to analyze correlations between diagnostic tests.
Results
None of the studied patient characteristics (age, gender, body mass index, smoking, sinonasal disease) was associated with TMM results except for pollen allergy (OR 1.74, 95% CI 1.15-2.63, P = 0.009). TMM results correlated with Valsalva maneuver performance (P < 0.001, ρ = 0.31) and otomicroscopic signs of inadequate middle ear ventilation (P < 0.001, ρ = 0.28). The Eustachian tube dysfunction questionnaire-7 (ETDQ-7) score did not correlate with any diagnostic method.
Conclusions
TMM results are unaffected by patient characteristics other than pollen allergy. Thus, TMM may be used in ETD diagnostics in a wide variety of patients with straightforward interpretation. TMM correlates with other diagnostic tests studied but not with ETDQ-7. ETDQ-7 does not seem to correlate with other diagnostic tests and appears nonspecific in ETD diagnostics.